Pengalaman Belajar Mahasiswa Dalam Model Pembelajaran Scl Di Program Studi Keperawatan Stikes Jenderal Achmad Yani Yogyakarta - Rahayu Iskandar; Deby Zulkarnain Rahadian Syah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2017)
Objective: Explores in depth the learning experience of students in SCL “student center learning” model in Nursing Program Stikes General Achmad Yani Yogyakarta. Methods: This research use qualitative method with descriptive approach, executed on June until August 2016 in Nursing Program Stikes General Achmad Yani Yogyakarta. Informants in this study were selected by purposive sampling technique of convenience sampling. The informants involved in this research are 6 informants, where the researcher has obtained the data saturation in gathering information and has reached redudancy. Interviews were conducted once for each participant, lasting approximately 60-90 minutes for each participant. Data analysis method used in this research is method of analysis from Colaizzi. Result: There are 12 themes perceived by Nursing Program Stikes General Achmad Yani Students about SCL learning model that is role of student, the role of lecturer, learning process, student expression with SCL learning model, the number of group members, student activeness in learning, improvement of student soft skills, means of learning, lecturer relationships with students, relationships between students, supporting factors, and inhibiting factors Conclusion: There are three perceptions of students about SCL learning, namely the role of lecturer as facilitator and mediator, scheduled learning process, and student perception on SCL learning model. The advantages of learning perceived by the students is seen from the number of group members, the activity of the students in learning and the improvement of the soft skills of the students. Lesson in the SCL learning model perceived by the students, the learning facilities, the relationship of lecturers with students, and the relationship among students. There are two factors that play a role in student learning in SCL learning model in Nursing Program Stikes General Achmad Yani Yogyakarta is the driving factor (self, family and friends)